The role of exercise and diet in maintaining bone health - Yoshiko Ishimi; Kaoru Yanaka (Japanese Society of Physical Fitness and Sports Medicine, 2012)
Prevention is the most important measure against osteoporosis, since bone mass, once it is lost, cannot be recovered. Bone mass, in both men and women, reaches a maximum level in the 20s to 30s age range, and maintains this level or slightly increases toward the 40s, and gradually decreases thereafter. In particular, bone mass dramatically decreases in postmenopausal women because of a decrease in serum estrogen level. Bone mass is influenced by genetic and environmental factors such as mechanical loading, nutrition, and lifestyle, besides gender, age, and metabolic factors. Among these factors, mechanical loading, i.e. exercise, and nutrition seem to be important in maintaining bone health, since they are expected to improve with changes in lifestyle. Routine exercise and a diet rich in minerals and vitamins, throughout life, both contribute to maintaining bone health.